HUBUNGAN LOVING TOUCH BABY MASSAGE BAYI DENGAN PENINGKATAN FREKUENSI MENYUSUI PADA BAYI - Yusmaharani; Siti Aisyah (LPPM Universitas Abdurrab, 2025)
Breast milk is an important nutrient for infant growth. Breast milk is given to infants during the first 6 months of life without any additional food intake. The benefits of breastfeeding include nutrition, increasing intelligence and increasing the bond of affection. Loving touch baby massage is a massage technique for infants that causes the baby to be more relaxed and can rest effectively so that when the baby wakes up it will bring enough energy to be active. Babies become hungry quickly when they are optimally active, so their appetite increases. Quasy experimental research method, with a design (Two Group). In this design there are groups that are compared (control and intervention) The results of this study in the intervention group infants during the pretest were the majority <8 times breastfeeding a day, namely 13 respondents (81.3%), while at the posttest the majority breastfed ≥ 8 times a day, namely 14 respondents (87.5%). in the control group infants during the pretest the majority <8 times breastfeeding a day, namely 13 respondents (81.3%), while at the posttest the most breastfed ≥ 8 times a day, namely 4 respondents (25.0%). Statistical Test using Mann-Whitney U Test. There is a Pvalue of 0.000 <0.05 which means there is a difference between the frequency of the control and intervention groups. This shows that there is an increase in the frequency of breastfeeding in infants with the Mann-Whitney U Test. Where in the intervention group there is an increase in the frequency of breastfeeding.